Outcomes, Healthcare Resource Utilization, and Costs of Overall, Community-Acquired, and Hospital-Acquired Acute Kidney Injury in COVID-19 Patients - Jay L. Koyner; Rachel H. Mackey; Ning A. Rosenthal; Leslie A. Carabuena; J. Patrick Kampf; Paul McPherson; Toni Rodriguez; Aarti Sanghani; Julien Textoris (Journal of Health Economics and Outcomes Research)
**Background:** In hospitalized patients with COVID-19, acute kidney injury (AKI) is associated with higher mortality, but data are lacking on healthcare resource utilization (HRU) and costs related to AKI, community-acquired AKI (CA-AKI), and hospital-acquired AKI (HA-AKI). **Objectives:** To quantify the burden of AKI, CA-AKI, and HA-AKI among inpatients with COVID-19. **Methods:** This retrospective cohort study included inpatients with COVID-19 discharged from US hospitals in the Premier PINC AI™ Healthcare Database April 1–October 31, 2020, categorized as AKI, CA-AKI, HA-AKI, or no AKI by ICD-10-CM diagnosis codes. Outcomes were assessed during index (initial) hospitalization and 30 days postdischarge. **Results:** Among 208 583 COVID-19 inpatients, 30%, 25%, and 5% had AKI, CA-AKI, and HA-AKI, of whom 10%, 7%, and 23% received dialysis, respectively. Excess mortality, HRU, and costs were greater for HA-AKI than CA-AKI. In adjusted models, for patients with AKI vs no AKI and HA-AKI vs CA-AKI, odds ratios (ORs) (95% CI) were 3.70 (3.61-3.79) and 4.11 (3.92-4.31) for intensive care unit use and 3.52 (3.41-3.63) and 2.64 (2.52-2.78) for in-hospital mortality; mean length of stay (LOS) differences and LOS ratios (95% CI) were 1.8 days and 1.24 (1.23-1.25) and 5.1 days and 1.57 (1.54-1.59); and mean cost differences and cost ratios were $7163 and 1.35 (1.34-1.36) and $19 127 and 1.78 (1.75-1.81) (all _P_ < .001). During the 30 days postdischarge, readmission LOS was ≥6% longer for AKI vs no AKI and HA-AKI vs CA-AKI; outpatient costs were ≥41% higher for HA-AKI vs CA-AKI or no AKI. Only 30-day new dialysis (among patients without index hospitalization dialysis) had similar odds for HA-AKI vs CA-AKI (2.37-2.8 times higher for AKI, HA-AKI, or CA-AKI vs no AKI). **Discussion:** Among inpatients with COVID-19, HA-AKI had higher excess mortality, HRU, and costs than CA-AKI. Other studies suggest that interventions to prevent HA-AKI could decrease excess morbidity, HRU, and costs among inpatients with COVID-19. **Conclusions:** In adjusted models among COVID-19 inpatients, AKI, especially HA-AKI, was associated with significantly higher mortality, HRU, and costs during index admission, and higher dialysis and longer readmission LOS during the 30 days postdischarge. These findings support implementation of interventions to prevent HA-AKI in COVID-19 patients.